Prospectively defined murine mesenchymal stem cells inhibit Klebsiella pneumoniae-induced acute lung injury and improve pneumonia survival. Issue 1 (December 2015) - Hackstein, Holger; Lippitsch, Anne; Krug, Philipp; Schevtschenko, Inna; Kranz, Sabine; Hecker, Matthias; Dietert, Kristina; Gruber, Achim; Bein, Gregor; Brendel, Cornelia; Baal, Nelli
Abstract Background Numerous studies have described the immunosuppressive capacity of mesenchymal stem cells (MSC) but these studies use mixtures of heterogeneous progenitor cells for in vitro expansion. Recently, multipotent MSC have been prospectively identified in murine bone marrow (BM) on the basis of PDFGRa+ SCA1+ CD45− TER119− (PαS) expression but the immunomodulatory capacity of these MSC is unknown. Methods We isolated PαS MSC by high-purity FACS sorting of murine BM and after in vitro expansion we analyzed the in vivo immunomodulatory activity during acute pneumonia. PαS MSC (1 × 106 ) were applied intratracheally 4 h after acute respiratoryKlebsiella pneumoniae induced infection. Results PαS MSC treatment resulted in significantly reduced alveolitis and protein leakage in comparison to mock-treated controls. PαS MSC-treated mice exhibited significantly reduced alveolar TNF-α and IL-12p70 expression, while IL-10 expression was unaffected. Dissection of respiratory dendritic cell (DC) subsets by multiparameter flow cytometry revealed significantly reduced lung DC infiltration and significantly reduced CD86 costimulatory expression on lung CD103+ DC in PαS MSC-treated mice. In the post-acute phase of pneumonia, PαS MSC-treated animals exhibited significantly reduced respiratory IL-17+ CD4+ T cells and IFN-γ+ CD4+ T cells. Moreover, PαS MSC treatment significantly improved overall pneumonia survival and did not increase bacterial load. Conclusion In this study we demonstrated for the first time the feasibility and in vivo immunomodulatory capacity of prospectively defined MSC in pneumonia.